MicroRNA-532 protects the heart in acute myocardial infarction, and represses prss23, a positive regulator of endothelial-to-mesenchymal transition. Issue 13 (11th July 2017) - Bayoumi, Ahmed S.; Teoh, Jian-Peng; Aonuma, Tatsuya; Yuan, Zhize; Ruan, Xiaofen; Tang, Yaoliang; Su, Huabo; Weintraub, Neal L.; Kim, Il-Man
Abstract: Aims: Acute myocardial infarction (MI) leads to cardiac remodelling and development of heart failure. Insufficient myocardial capillary density after MI is considered a critical determinant of this process. MicroRNAs (miRs), negative regulators of gene expression, have emerged as important players in MI. We previously showed that miR-532-5p (miR-532) is up-regulated by the β-arrestin-biased β-adrenergic receptor antagonist (β-blocker) carvedilol, which activates protective pathways in the heart independent of G protein-mediated second messenger signalling. Here, we hypothesize that β2 -adrenergic receptor/β-arrestin-responsive miR-532 confers cardioprotection against MI. Methods and results: Using cultured cardiac endothelial cell (CEC) and in vivo approaches, we show that CECs lacking miR-532 exhibit increased transition to a fibroblast-like phenotype via endothelial-to-mesenchymal transition (EndMT), while CECs over-expressing miR-532 display decreased EndMT. We also demonstrate that knockdown of miR-532 in mice causes abnormalities in cardiac structure and function as well as reduces CEC proliferation and cardiac vascularization after MI. Mechanistically, cardioprotection elicited by miR-532 is in part attributed to direct repression of a positive regulator of maladaptive EndMT, prss23 (a protease serine 23) in CECs. Conclusions: In conclusion, these findings reveal a pivotal role for miR-532-prss23 axis in regulating CEC function after MI, and this novel axis could be suitable for therapeutic intervention in ischemic heart disease.